Nanomagnetic Particle Production: Effect of Carbon and Iron Sources - M.T.A.P. Kresnowati; Andy Wiranata Wijaya; Andry Andry (Institute for Research and Community Services, Institut Teknologi Bandung, 2016)
Production of nanomagnetic particles via microbial processes offers the advantage of better biocompatibility for medical applications. However, this process is not widely applied due to the difficulties in cultivating magnetotactic bacteria in the lab. This research explored the possibilities of cultivating magnetotactic bacteria in order to produce nanomagnetic particles in the lab and in particular to find the carbon and iron sources to get the optimum yield of nanomagnetic particles. Experiments were performed as semiaerobic-batch-magnetotactic-bacteria cultivations. The carbon source in the media was varied as: sodium lactate, sodium acetate, and sodium pyruvate. As for the iron source, either Fe-citrate or Fe-quinate was used. Bacterial cell growth was monitored using the turbidometry-gravimetry method, substrate concentration was measured using high performance liquid chromatography (HPLC), while the cellular iron content was measured using electron dispersive X-ray spectroscopy (EDS) and transmission electronic microscopy (TEM). It was observed that cell growth did not correlate with the production of nanomagnetic particles. The bacteria grew best on sodium pyruvate and Fe-quinate, however, the best yield of nanomagnetic particles was obtained from the cultivation with sodium acetate and Fe-quinate. The obtained TEM images confirmed the presence of nanomagnetic particles.